Nickel-Cadmium Battery Analysis Using Spectrogram - Kasim, Rizanaliah; Abdullah, Abdul Rahim; Selamat, Nur Asmiza; Mohamad Basir, Muhammad Sufyan Safwan; Ramli, Mohd Zulkifli (Asian Research Publishing Network (ARPN), 2016)
-